Cranio-Orbito-Zygomatic Approach - Luzzi, Sabino; Giotta Lucifero, Alice; Bruno, Nunzio; Baldoncini, Matias; Campero, Alvaro; Galzio, Renato (Acta Biomedica Atenei Parmensis, 2022)
The cranio-orbito-zygomatic (COZ) approach consists of an extension of the pterional approach characterized by the removal of the superolateral part of the orbital rim and zygoma. This key step tremendously increases the angular exposure to some deep targets and overall surgical freedom to the lesion.In this article we review the technical variations of the COZ approach, mainly focusing on the differential quantitative effects coming from the orbital osteotomy compared to the zygomatic one.